2021
DOI: 10.1186/s12932-021-00075-1
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution and solubility of calcite-rhodochrosite solid solutions [(Ca1-xMnx)CO3] at 25 °C

Abstract: A complete series of calcite-rhodochrosite solid solutions [(Ca1-xMnx)CO3] are prepared, and their dissolution processes in various water samples are experimentally investigated. The crystal morphologies of the solid solutions vary from blocky spherical crystal aggregates to smaller spheres with an increasing incorporation of Mn in the solids. Regarding dissolution in N2-degassed water, air-saturated water and CO2-saturated water at 25 °C, the aqueous Ca and Mn concentrations reach their highest values after 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Understanding the paragenetic sequence of carbon mineralization assemblages, including silica and aluminosilicate precipitation, will aid in the development and parametrization of predictive models, critical during permitting and monitoring stages of a carbon storage operation. Additionally, clarifying carbonate nodule compositional variability is crucial for predicting carbonate stability, as trace components and zonation may lead to distinct preferential nucleation and dissolution behavior. , Lastly, although the complex carbonate nodules may have exotic compositions, textures, and chemical zonation trends, their widespread presence in the Wallula samples and basalt carbonation experiments highlights their broad importance for continued CDR via CO 2 sequestration in reactive reservoirs.…”
Section: Environmental Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding the paragenetic sequence of carbon mineralization assemblages, including silica and aluminosilicate precipitation, will aid in the development and parametrization of predictive models, critical during permitting and monitoring stages of a carbon storage operation. Additionally, clarifying carbonate nodule compositional variability is crucial for predicting carbonate stability, as trace components and zonation may lead to distinct preferential nucleation and dissolution behavior. , Lastly, although the complex carbonate nodules may have exotic compositions, textures, and chemical zonation trends, their widespread presence in the Wallula samples and basalt carbonation experiments highlights their broad importance for continued CDR via CO 2 sequestration in reactive reservoirs.…”
Section: Environmental Implicationsmentioning
confidence: 99%
“…Additionally, clarifying carbonate nodule compositional variability is crucial for predicting carbonate stability, as trace components and zonation may lead to distinct preferential nucleation and dissolution behavior. 92,93 Lastly, although the complex carbonate nodules may have exotic compositions, textures, and chemical zonation trends, their widespread presence in the Wallula samples and basalt carbonation experiments highlights their broad importance for continued CDR via CO 2 sequestration in reactive reservoirs.…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%
“…Beginning with Engel in 1889, many researchers have studied the solubility of calcite under different conditions [31,32]. The pK sp (298.15 K) values of calcite are reported to be around 8.40 [33,34].The saturated solution compositions of fluorite and calcite are shown in Figure 2 [35].…”
Section: Solubilitymentioning
confidence: 99%
“…Beginning with Engel in 1889, many researchers have studied the solubility of calcite under different conditions [31,32]. The pKsp (298.15 K) values of calcite are reported to be around 8.40 [33,34].The saturated solution compositions of fluorite and calcite are shown in Figure 2 As illustrated in the diagrams, the main components of fluorite within the pH8-10 (conventional fluorite flotation pH range) are Ca 2+ and F − , and the main components of calcite are Ca 2+ , CO3 2− and HCO3 − .The results of solution chemistry calculations and XPS spectral analysis in several previous studies [36,37] showed that the dissolved F − and CO3 2− can adsorb on the surface of calcite and fluorite, respectively and form the corresponding calcium-containing compounds, which homogenizes the chemical properties of fluorite and calcite surfaces. The surface properties homogenization phenomenon of fluorite and calcite can occur not only in solution but also in the solid-phase grinding process.…”
Section: Peer Reviewmentioning
confidence: 99%